Socioeconomic inequalities in maternal health care utilization in Ghana - Jacob Novignon; Bernice Ofori; Kwasi Gyabaa Tabiri; Mohammad Habibullah Pulok (BMC, 2019)
Abstract Background Improving maternal and child health remains a public health priority in Ghana. Despite efforts made towards universal coverage, there are still challenges with access to and utilization of maternal health care. This study examined socioeconomic inequalities in maternal health care utilization related to pregnancy and identified factors that account for these inequalities. Methods We used data from three rounds of the Ghana Demographic and Health Surveys (2003, 2008 and 2014). Two health care utilization measures were used; (i) four or more antenatal care (ANC) visits and (ii) delivery by trained attendants (DTA). We first constructed the concentration curve (CC) and estimated concentration indices (CI) to examine the trend in inequality. Secondly, the CI was decomposed to estimate the contribution of various factors to inequality in these outcomes. Results The CCs show that utilization of at least four ANC visits and DTA were concentrated among women from wealthier households. However, the trends show the levels of inequality decreased in 2014. The CI of at least four ANC visits was 0.30 in 2003 and 0.18 in 2014. Similarly, the CIs for DTA was 0.60 in 2003 and 0.42 in 2014. The decomposition results show that access to National Health Insurance Scheme (NHIS) and women's education levels were the most important contributors to the reduction in inequality in maternal health care utilization. Conclusions The findings highlight the importance of the NHIS and formal education in bridging the socioeconomic gap in maternal health care utilization.